2016
DOI: 10.1002/tox.22256
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and ERα enhanced β‐catenin degradation and suppressed its downstream target genes to block the metastatic function of HA22T hepatocellular carcinoma cells via modulating GSK‐3β and β‐TrCP expression

Abstract: In our previous experiments, we found β-catenin was highly expressed in the tumor area with high invasive ability and poor prognosis. In this study, we have examined the mechanism by which ERα regulates β-catenin expression as well as the metastasis ability of hepatocellular cancer HA22T cells. To identify whether the anticancer effect of estrogen and ERα is mediated through suppression of β-catenin expression, we co-transfected pCMV-β-catenin and ERα into HA22T cells, and determined the cell motility by wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The ERa is mainly activated by estrogen to regulate a wide range of cellular activities in response to estrogen [20]. Recent studies have shown that in HA22T cells, ERa binds to GSk-3b and induced ubiquitination and degradation of b-catenin in a ligand-dependent manner [21,22]. Our studies show that GSK-3b and c-MYC can be induced by estrogen in ovariectomized mouse while estrogen can reduce nuclear b-catenin expression.…”
Section: Discussionsupporting
confidence: 52%
“…The ERa is mainly activated by estrogen to regulate a wide range of cellular activities in response to estrogen [20]. Recent studies have shown that in HA22T cells, ERa binds to GSk-3b and induced ubiquitination and degradation of b-catenin in a ligand-dependent manner [21,22]. Our studies show that GSK-3b and c-MYC can be induced by estrogen in ovariectomized mouse while estrogen can reduce nuclear b-catenin expression.…”
Section: Discussionsupporting
confidence: 52%
“…The binding of ERα with β-catenin was enhanced by estrogen, which activated the binding of β-catenin with E3 ligase to promote its degradation and block the metastasis in HCC cells. 24 Considering that liver cancer is more prevalent in males, the possible mechanism associated with a negative correlation between Wls and ER-negative breast cancer still needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Moreover, a multitude of studies have shown that the expression of ERα in primary HCC tissues is decreased compared to normal liver tissues or the adjacent tissues, which indirectly confirmed the suppressive effects of ERα in HCC. [13][14][15] In light of this anti-tumor effect of ERα in HCC, reactivating ERα signaling can offer a new therapeutic strategy in HCC prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%